2000
DOI: 10.1002/pen.11180
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strain rate, temperature, and molecular mass on the tensile deformation of polyethylene

Abstract: Conventional tensile testing applied to high density polyethylene can lead to erroneous impressions of the tensile response of the material due to a local reduction in cross section of the sample. Several workers have developed novel tensile testing techniques to measure the response of a small element as it deforms. The true stress true strain curve that results describes tensile deformation of the material in a geometry‐independent manner. Here, results from previous workers, together with some of our own, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Although both the experimental and theoretical results demonstrate that the sheet temperature increases by a few degrees during biaxial stretching, this slight increase in temperature is unlikely to influence the relaxation of polymer chains. ΔT=βεσCPCdε where βε is the effective thermal plastic work conversion factor ( βε ∼ 1) , dε is the differential of strain ε, CPC is the heat capacity of the carbon nanofiller reinforced composite, which are 2,184, 2,188, and 2,188 J/(kg K) for the HDPE/MWCNT, HDPE/GNP, and HDPE/CB composites from the mixture rule .…”
Section: Resultsmentioning
confidence: 99%
“…Although both the experimental and theoretical results demonstrate that the sheet temperature increases by a few degrees during biaxial stretching, this slight increase in temperature is unlikely to influence the relaxation of polymer chains. ΔT=βεσCPCdε where βε is the effective thermal plastic work conversion factor ( βε ∼ 1) , dε is the differential of strain ε, CPC is the heat capacity of the carbon nanofiller reinforced composite, which are 2,184, 2,188, and 2,188 J/(kg K) for the HDPE/MWCNT, HDPE/GNP, and HDPE/CB composites from the mixture rule .…”
Section: Resultsmentioning
confidence: 99%
“…Although the strain rate at which an experiment may be considered adiabatic depends on both material properties and specimen size, for typical tests on polymers it may be of the order 0.01-1 s -1 [94]. Important studies involving the temperature rise in specimens during high rate deformation have been conducted by a number of authors [95][96][97][98][99][100][101]. A notable achievement was by Chou et al [95], who showed that the temperature rise in specimens increases significantly after yield.…”
Section: Dynamic Loading: Split Hopkinson Pressure Barmentioning
confidence: 99%
“…Good agreement was observed between the experimentally measured temperature rise and the ''theoretical'' rise obtained by assuming that 100 % of the mechanical work is converted to heat and adiabatic conditions prevail. Hillmansen et al [98,99] studied plastic work being converted to heat by studying high density polyethylene (HDPE) and found, similarly, that the plastic work at large strains was approximately 100 % converted to heat.…”
Section: Dynamic Loading: Split Hopkinson Pressure Barmentioning
confidence: 99%
“…Only a few workers [8][9][10][11][12] have overcome this problem by measuring in real time the cross-section area at the center of the neck by means of mechanical or optical transducers. As such, under the assumption of constant density, they were capable of deriving the response of the material within a very small representative volume element (RVE) in which stresses and strains are supposed to be nearly homogeneous.…”
Section: Introductionmentioning
confidence: 99%